2022
DOI: 10.3390/polym14061080
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Cellulose and Its Applications

Abstract: The sharp increase in the use of cellulose seems to be in increasing demand in wood; much more research related to sustainable or alternative materials is necessary as a lot of the arable land and natural resources use is unsustainable. In accordance, attention has focused on bacterial cellulose as a new functional material. It possesses a three-dimensional, gelatinous structure consisting of cellulose with mechanical and thermal properties. Moreover, while a plant-originated cellulose is composed of cellulose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
58
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(61 citation statements)
references
References 214 publications
0
58
0
3
Order By: Relevance
“…However, most of these materials have restrictions, for example, a lack of antibacterial activity and low mechanical properties [ 135 ]. Recently, several reviews on BC materials for biomedical applications have been reported [ 18 , 19 , 20 , 21 , 22 , 143 , 144 , 145 , 146 , 147 ], and a summary of various biomedical applications of BC and BC-based composites developed through different strategies is provided in Table 2 .…”
Section: Bc-based Nanocompositesmentioning
confidence: 99%
See 2 more Smart Citations
“…However, most of these materials have restrictions, for example, a lack of antibacterial activity and low mechanical properties [ 135 ]. Recently, several reviews on BC materials for biomedical applications have been reported [ 18 , 19 , 20 , 21 , 22 , 143 , 144 , 145 , 146 , 147 ], and a summary of various biomedical applications of BC and BC-based composites developed through different strategies is provided in Table 2 .…”
Section: Bc-based Nanocompositesmentioning
confidence: 99%
“…Recently, a series of commercial medical materials based on BC has been obtained such as Biofill ® (Curitiba, Brazil) and Bioprocess ® (Curitiba, Brazil) for the therapy of burns and ulcers, Gengiflex ® (Curitiba, Brazil) to treat periodontal diseases, Dermafill ® (Londrina, Brazil) for effective wound-healing burns and ulcers, Membracel ® (Curitiba, Brazil) for venous leg ulcers and lacerations, xCell ® (New York, NY, USA) to treat chronic wounds, EpiProtect ® (Royal Wootton Bassett, UK) for burn wounds, and Nanoskin ® (São Carlos, Brazil) (the antimicrobial BC product incorporated with silver ions) [ 20 , 193 ]. By the product form and a method of administration, wound dressings are divided into: films, hydrogels, sponges, foams, fiber scaffolds, bandages ( Figure 7 ) [ 185 ].…”
Section: Bc-based Nanocompositesmentioning
confidence: 99%
See 1 more Smart Citation
“…Since cellulosic is considered "generally recognized as safe" (GRAS) by the Food and Drug Administration (FDA), it possess great potential in food products due to its various textures and easy production process, several recent food products are good to be kept in view, as cellulosic SCOBY can be applied food applications (Table 4). Food additive [66] Ice cream Thickener [67] Low-fat sausage Dietary food [68] The cellulosic SCOBY, which associated with bacterial cellulose fibrils secrete a unique hydrogellike substance with attributes that are being used in the numerous food industries. In spite of the interest shown in food applications, SCOBY can be a great potential as a sustainable substitute in fashion and automobile device industries.…”
Section: Recent Scoby Induced Food Productsmentioning
confidence: 99%
“…Biomolecules such as starch, bacterial cellulose, and gelatin have been used to develop packaging materials [ 2 ]. These packaging materials are considered biodegradable, sustainable, and environmentally friendly [ 3 , 4 ]. However, some disadvantages must be overcome, such as their high hydrophilicity, low water vapor, gas, and light barrier, and low mechanical resistance [ 1 , 5 ].…”
Section: Introductionmentioning
confidence: 99%